Combined Induction of Rubber-Hand Illusion and Out-of-Body Experiences - Olivé, Isadora; Berthoz, Alain (Frontiers in Psychology, 2012)
The emergence of self-consciousness depends on several processes: those of body ownership, attributing self-identity to the body, and those of self-location, localizing our sense of self. Studies of phenomena like the rubber hand illusion (RHi) and out-of-body experience (OBE) investigate these processes, respectively for representations of a body-part and the full-body. It is supposed that RHi only target processes related to body-part representations, while OBE only relates to full-body representations. The fundamental question whether the body-part and the full-body illusions relate to each other is nevertheless insufficiently investigated. In search for a link between body-part and full-body illusions in the brain we developed a behavioural task combining adapted versions of the RHi and OBE. Furthermore, for the investigation of this putative link we investigated the role of sensory and motor cues. We established a spatial dissociation between visual and proprioceptive feedback of a hand perceived through virtual reality in rest or action. Two experimental measures were introduced: one for the body-part illusion, the proprioceptive drift of the perceived localisation of the hand, and one for the full-body illusion, the shift in subjective-straight-ahead. In the rest and action conditions it was observed that the proprioceptive drift of the left hand and the shift in subjective-straight-ahead towards the manipulation side are equivalent. The combined effect was dependent on the manipulation of the visual representation of body-parts, rejecting any main or even modulatory role for relevant motor programs. Our study demonstrates for the first time that there is a systematic relationship between the body-part illusion and the full-body illusion, as shown by our measures. This suggests a link between the representations in the brain of a body-part and the full-body, and consequently a common mechanism underpinning both forms of ownership and self-location.